Comment: COVID-19 outbreak and the practice of surgery: do we need to change? - Sonmez, Kaan (Br J Surg, 2021)
We aim to relate our practice during the COVID-19 pandemic between March 17 and May 17, 2020 in our pediatric surgery department.